2018
DOI: 10.1175/jcli-d-17-0445.1
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Causes for the Changing Behavior of the Tropical Indian Ocean in the Past Few Decades

Abstract: Observations show that decadal (10–20 yr) to interdecadal (>20 yr) variability of the tropical Indian Ocean (TIO) sea surface temperature (SST) closely follows that of the Pacific until the 1960s. Since then, the TIO SST exhibits a persistent warming trend, whereas the Pacific SST shows large-amplitude fluctuations associated with the interdecadal Pacific oscillation (IPO), and the decadal variability of the TIO SST is out of phase with that of the Pacific after around 1980. Here causes for the changing beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 45 publications
3
34
0
Order By: Relevance
“…Significant IOD influence on ENSO found in several models shows an agreement with past studies (e.g., Cai et al, 2011;Jourdain et al, 2016;Luo et al, 2010;Santoso et al, 2012). The results described here show a support for the suggestion in previous studies (e.g., Zhang, Han, & Sienzn, 2018) that the IOD is more active and is having greater influence on global climate. While natural external forcing (i.e., volcanic forcing) and global warming make the IO more active, the warming trend over the IO is the main contributor and mostly in phase with the trend of the global mean SST (Roxy et al, 2014).…”
Section: The Future Influence Of the Iod On Ensosupporting
confidence: 92%
See 1 more Smart Citation
“…Significant IOD influence on ENSO found in several models shows an agreement with past studies (e.g., Cai et al, 2011;Jourdain et al, 2016;Luo et al, 2010;Santoso et al, 2012). The results described here show a support for the suggestion in previous studies (e.g., Zhang, Han, & Sienzn, 2018) that the IOD is more active and is having greater influence on global climate. While natural external forcing (i.e., volcanic forcing) and global warming make the IO more active, the warming trend over the IO is the main contributor and mostly in phase with the trend of the global mean SST (Roxy et al, 2014).…”
Section: The Future Influence Of the Iod On Ensosupporting
confidence: 92%
“…In addition, IOD events might be induced by the low-frequency variability of thermocline (Zhang, Du, et al, 2018). Furthermore, future IOD changes might be influenced by anthropogenic forcing and volcanic forcing (Zhang, Han, et al, 2018). Figure 1).…”
Section: Figures S2a S2bmentioning
confidence: 99%
“…The different interbasin warming contrast across different ensemble members of CESM‐LE is mainly due to variations in the simulated Pacific Ocean warming trend, which is due to the influence of the Interdecadal Pacific Oscillation (IPO). The spread of the Indian Ocean warming in CESM‐LE is much smaller, indicating that the anthropogenic warming trend dominates its relatively weak decadal variability (Zhang et al, ). By contrast, in the CMIP5 models, magnitudes of the warming trends in the two ocean basins are tightly linked, with a large (small) Indian Ocean warming corresponding to a large (small) Pacific Ocean warming, which may be related to different model sensitivities to the anthropogenic GHG forcing.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of climate models that participated in the Coupled Model Intercomparison Project phase 5 (CMIP5) simulated an El Niño-like sea surface temperature (SST) warming pattern in response to GHG forcing, with a larger warming appearing in the eastern tropical Pacific relative to the western tropical Pacific (Figure 1d; Vecchi & Soden, 2007b;Xie et al, 2010;Zhang & Li, 2014). The long-term SST trends in observational data sets, however, exhibit different patterns from those in the CMIP5 models (Coats & Karnauskas, 2017;Zhang, 2016;Zhang et al, 2018). While some observational data sets show a weak La Niña-like SST trend pattern with a small negative SST trend in the eastern tropical Pacific (Figures 1a and 1b), others show negligible changes in the zonal SST gradient (Figures 1c and S1; Solomon & Newman, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The hiatus has attracted great attention because it contrasts with the steady increasing trend of greenhouse gas emissions, and various mechanisms have been proposed to explain it. Numerous studies have suggested that the hiatus is a decadal climate fluctuation or variation induced by radiative forcing (Lean and Rind, ), upper or deep ocean heat uptake (Chen and Tung, ; Nieves et al , ), or internal variability modes of the climate system including the El Niño‐Southern Oscillation (ENSO), the North Atlantic Oscillation (NAO), the Pacific Decadal Oscillation (PDO)/Interdecadal Pacific Oscillation (IPO), and the Atlantic Multidecadal Oscillation (AMO) (Kosaka and Xie, , ; England et al , ; Dai et al , ; Steinman et al , ; Zhang, ; Yao et al , ; Zhang et al , ). Mechanistically, a negative phase of PDO/IPO leads to an unprecedented acceleration of the Walker circulation via strengthening of the trade wind in the central‐eastern tropical Pacific, resulting in a La Niña‐like cooling which contributes to the hiatus (Kosaka and Xie, ; McGregor et al , ).…”
Section: Introductionmentioning
confidence: 99%